Risk and timing of venous thromboembolism in patients with gastrointestinal cancer: a nationwide Danish cohort study. Issue 1 (19th January 2023) - Tønnesen, Jacob; Pallisgaard, Jannik; Rasmussen, Peter Vibe; Ruwald, Martin H; Lamberts, Morten; Nouhravesh, Nina; Strange, Jarl; Gislason, Gunnar Hilmar; Hansen, Morten Lock
Abstract : Aims: Cancer is a well-known risk factor of venous thromboembolism (VTE). Some cancers are believed to be more thrombogenic. The purpose of this study was to investigate the characteristics of patients with incident gastrointestinal cancers (GI) and their associated 1-year risk and timing of venous thromboembolic events and the 1-year mortality. Methods: This study was a retrospective cohort study. Through Danish nationwide registries, all patients with first-time GI cancer diagnosis from 2008 to 2018 were identified. Incident VTE events were identified within a 1-year follow-up after GI cancer diagnosis using the Aalen-Johansen estimator. Cox proportional-hazard models were applied to investigate risk factors for VTE events and the impact of VTE on mortality. Results: A total of 87 069 patients were included and stratified by cancer types: liver (5.8%), pancreatic (12.0%), gastric (6.9%), small intestinal (1.9%), colorectal (61.8%), oesophageal (7.3%) and gallbladder (3%). Most VTE events happened close to onset of the cancer diagnosis with declining events by time. The 1-year cumulative incidence of VTE differed according to cancer type with pancreatic cancer being most thrombogenic (7.8%), and colorectal and liver cancer being the least (3.6%). Prior VTE, heart failure, chronic obstructive pulmonary disease (COPD), liver disease, chronic kidney disease (CKD) and diabetes increased the VTE risk. Overall, the patients with GI cancer had high 1-year mortality of 33.3% with patients with pancreatic cancer having the highest mortality (70.3%). Conclusion: We found that most VTE events happen close to onset of the GI cancer diagnosis and thrombogenicity differed by type of GI cancer, ranging from 7.8% in patients with pancreatic cancer to 3.6% in colorectal and patients with liver cancer. Prior VTE, heart failure, COPD, liver disease, CKD and DM were associated with increased risk of VTE.